On quasi-Lamb waves in the system "half-space of a viscous fluid — compressible elastic layer with initial stresses" - Guz, A.N.; Bahno, A.M. (Reports of the National Academy of Sciences of Ukraine, 2017)
The dispersion curves of quasi-Lamb waves in a hydroelastic system are constructed over a wide range of frequencies using the three-dimensional equations of the elasticity theory of finite deformations for a solid body and three-dimensional linearized Navier—Stokes equations for a viscous compressible fluid. The influence of initial stresses in the pre-deformed compressible elastic layer and of the half-space of the viscous compressible fluid on the phase velocities and attenuation coefficients of quasi-Lamb waves in a hydroelastic waveguide is analy zed. The localization properties of the lower quasi-Lamb modes in elastic-fluid waveguides are studied. For the wave processes, the approach developed and results obtained make it possible to establish the limits, within which the models based on the different variants of the theory of small initial deformations, classical elasticity theory, and the model of ideal fluid can be applied. The numerical results are presented in the form of graphs and their analysis is given.